A woman empowered with the power of love: A study of Alu in The Swamp Dwellers by Wole Soyinka - Uddin, Md Abu Saleh Nizam (IIUC Studies, 2022)
The Swamp Dwellers by Wole Soyinka (born, 1934) is mostly discussed for the emphasis it puts on the strong family ties felt by all the characters, presence of the elements of the absurd drama, corruption by the priests and human-nature relationship. But the powerful character Alu is also an area to concentrate on. She is a powerful woman with the power of love. This virtue of love she receives from her instinct, and her African tradition turns her into a powerful woman. Thus empowered, she plays her role in family, society, religion and nature. In the modern world where utmost cruelty looms large everywhere, love-empowered Alu is an example for positive change. Thus, this paper aims at exploring how Alu in The Swamp Dwellers is an empowered woman with love, who simultaneously receives her rights and does her duties in family and society, and nurtures deep feeling for religion and nature, and becomes an example to inspire humanity in a world of human catastrophes. IIUC Studies Vol.19, December 2022: 69-86